2020
DOI: 10.3389/fpsyt.2020.00805
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Mechanisms in Irritable Bowel Syndrome

Abstract: Irritable bowel syndrome (IBS) is a brain-gut axis disorder characterized by abdominal pain and altered bowel habits. IBS is a multifactorial, stress-sensitive disorder with evidence for familial clustering attributed to genetic or shared environmental factors. However, there are weak genetic associations reported with IBS and a lack of evidence to suggest that major genetic factor(s) contribute to IBS pathophysiology. Studies on animal models of stress, including early life stress, suggest a role for environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 159 publications
(178 reference statements)
0
26
0
4
Order By: Relevance
“…This finding provided a novel insight regarding COVID-19 stress management at HIV clinics, particularly on the importance of institutional support. Previous studies showed that healthcare providers in supportive working environments were inclined to exhibit greater resilience-related abilities, including emotional regulation [ 47 ], self-efficacy [ 48 ], and adaptive coping strategies [ 49 ]. In facing a public health emergency, sufficient institutional support might enable HIV healthcare providers to use their internal coping recourses (i.e., resilience) and facilitate providers’ adaptive coping instead of being overwhelmed to deal with COVID-19 stressors, resulting in reduced levels of distress.…”
Section: Discussionmentioning
confidence: 99%
“…This finding provided a novel insight regarding COVID-19 stress management at HIV clinics, particularly on the importance of institutional support. Previous studies showed that healthcare providers in supportive working environments were inclined to exhibit greater resilience-related abilities, including emotional regulation [ 47 ], self-efficacy [ 48 ], and adaptive coping strategies [ 49 ]. In facing a public health emergency, sufficient institutional support might enable HIV healthcare providers to use their internal coping recourses (i.e., resilience) and facilitate providers’ adaptive coping instead of being overwhelmed to deal with COVID-19 stressors, resulting in reduced levels of distress.…”
Section: Discussionmentioning
confidence: 99%
“…79 There is some evidence for epigenetic changes in IBS, including alterations in DNA methylation, and various miRNAs appear to be associated with increased visceral sensitivity and permeability. 80…”
Section: Genetics and Epigeneticsmentioning
confidence: 99%
“…Previous studies evidenced that loss of functional activity of the GI pacemaking cells including, ICCs, SMCs, enteric neurons, platelet-derived growth factor receptor alpha positive (PDGFRα + ), and immune cells are driving forces contributing to the pathogenesis of DGBIs [10,23,29,31,50]. Cellular dysfunction in GI cells mediated via dysregulation of miRNAs likely regulates a variety of gut physiological and pathophysiological mechanisms leading to the development of diseases such as DGBIs [51,52]. Approximately 60% of protein coding mRNAs are modulated by miRNAs, including many of the key proteins associated with diseases [41,53].…”
Section: Functional Role Of Mirnas In Gut Physiological Mechanismsmentioning
confidence: 99%